A színpercepció és a színértelmezés online mérésének lehetőségei kisiskolás korban - Tóth, Alisa; Kárpáti, Andrea; Molnár, Gyöngyvér (Magyar Pedagógia, 2017)
Communication today is dominated by visual language, an important communication resource of which is colour (Kress & Van Leeuwen, 2002). The plethora of digital environments, images, animations, and videos are posing new challenges to visual educators and researchers, creating new demands for research-based development of visual skills (Bleed, 2005). Perception and interpretation of colour are important subcompetences of visual literacy. Related knowledge and skills are important parts of the Hungarian National Core Curriculum (2012). However, we still see a lack of either an elaborated description of colour perception and interpretation as subcompetences or research-based suggestions for their development at elementary level. The pilot study reported here offers a model of colour perception and interpretation as well as a battery of online colour perception and interpretation tasks that was piloted and found valid and reliable for 1st - and 2nd -graders (N=84; girls: 53%). The instrument consists of 62 items (Cronbach’s α=0.92). We found significant differences between the two age groups (age range: 6–6.5 and 7–7.8 years); (t=-4.7, p<0.001). Differences were detected in all subtests: colour sensitivity (t=-2.7, p<0.001), colour and form recognition (t=-3.9, p<0.001), colour memory (t=4.4, p<0.001), and colour and meaning (t=-2.8, p<0.001). The results show the developmental differences, but in order to explore the full range of development options and functioning modes of visual skills and abilities related to colour, future test development should involve higher age groups and explore various developmental strategies.